Thinking style in students of fifth year of secondary from different socioeconomic levels of the city of Lima - Caycho R., Tomas (2010)
We performed a comparative descriptive study aimed to explore differences in thinking styles in a sample of adolescent students in fifth year of secondary education in Metropolitan Lima from different socioeconomic levels. The instruments used for the study were the questionnaire Sternberg’s Thinking Style - Wagner Short Form, and the Socioeconomic Scale. The results show that thinking styles are rated as legislative, external and liberal, while less valued styles are style oligarchic, internal and the conservatives. Differences were found between students of different socioeconomic levels in terms of thinking styles legislative, executive, monarchist, anarchist, hierarchical, oligarchic, global, local, internal, external, liberal and conservative. Likewise, in the gender comparison, significant differences were found between men and women in styles legislative, executive, judicial, monarchist, hierarchy, local, external, liberal and conservative.